Relationship Between Self-Regulation and Math Self-Efficacy in Students of Sman 1 2x11 Enam Lingkung - Putra, Yudhi Pratama; Rinaldi (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Changes in education that are so rapid, if not accompanied by good adaptation skills by students, can cause anxiety, namely the fear of not achieving what is desired, such as anxiety, fear, worry, unwillingness to learn, boredom when following learning, and fear of not passing. Maths is a subject that is considered difficult, causing anxiety and worry. Although maths has been taught from primary school to university. However, there are still many students who think that mathematics is a very difficult subject and difficult to understand, especially those related to the formulas. This is what happens to students of SMAN 1 2x11 Enam Lingkung, therefore researchers are interested in examining the relationship between self-regulation and math self-efficacy in students of SMAN 1 2x11 Enam Lingkung. This study aims to determine the relationship between math self-efficacy and self-regulation in high school students. The method used is quantitative with correlational quantitative design. The research subjects were 112 students of SMAN 1 2x11 Enam Lingkung, with purposive sampling technique. The results of the analysis found that the relationship between the variables of math self-efficacy and self-regulation is linear, therefore the two variables can be tested using analysis.